Relationship of Parental Care With Academic Achievement of Junior High School Students - By Tri Agung Nusantara Kr. J. Tompong (CV. Get Press Indonesia, 2025)
Student academic achievement is one of the indicators of success in the formal education process. Various factors can affect a student's academic achievement, both from the school environment and the family environment. One of the important factors of the family environment is the parenting style of the parents. Purpose: this study aims to determine the relationship between parenting patterns of parents and academic achievement of students of junior high school (SMTP). Methods: the method used is a quantitative approach with correlational design. The sample was 75 Junior High School students who were randomly selected from several schools in the study area. Data were collected through questionnaires about parental parenting styles and documentation of students ' academic grades. Results the results of the analysis showed a significant relationship between authoritative parenting patterns with higher academic achievement, while permissive and authoritarian parenting patterns tend to correlate with lower achievement. Implications: the implications of this study indicate the importance of the role of parents in supporting children's learning process through a parenting approach that is balanced between control and warmth. Conclusion: parental care plays an important role in determining the academic success of Junior High School students, so efforts to improve the quality of care needs to be a common concern between families and educational institutions.